2004
DOI: 10.1002/bit.20258
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative effects of thermal injury and insulin on the metabolism of the skeletal muscle using the perfused rat hindquarter preparation

Abstract: Injury from a severe burn or trauma can propel the body into a hypermetabolic state that can lead to the significant erosion of lean muscle mass. Investigations describing this process have been somewhat limited due to the lack of adequate experimental models. Here we report the use of a perfused rat hindquarter preparation to study the consequences of a moderate burn injury (approximately 20% total body surface area), with or without the addition of exogenous insulin (12.5 mU/mL), on the fluxes of major metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 80 publications
(129 reference statements)
0
14
0
Order By: Relevance
“…The role of these factors could be investigated by changing substrate and hormone levels in the perfusate from the physiological to the pathological range. By coupling the biochemical measurements with MFA, we were able to gain a more comprehensive view of the metabolic state of the organ, as we have done previously in both liver [35,43,45] and skeletal muscle [48].…”
Section: Discussionmentioning
confidence: 90%
“…The role of these factors could be investigated by changing substrate and hormone levels in the perfusate from the physiological to the pathological range. By coupling the biochemical measurements with MFA, we were able to gain a more comprehensive view of the metabolic state of the organ, as we have done previously in both liver [35,43,45] and skeletal muscle [48].…”
Section: Discussionmentioning
confidence: 90%
“…CLP has also been shown to reduce the hepatic energy charge due to decreased function of mitochondria (Chen et al, 2004;Hampton et al, 1987;Hsieh et al, 2004). Since many transport mechanisms indirectly derive their energy Prior studies have also suggested that in a hypermetabolic state, a large flux of amino acids is generated from the catabolism of the skeletal muscle (Banta et al, 2004;Demling and Seigne, 2000). Both Sham-CLP and Burn-CLP treatment induced delayed gain and even loss of weight (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Prior studies using isolated perfused organs have identified differences in metabolic fluxes within liver Lee et al, 2000;Yamaguchi et al, 1997) and muscle (Banta et al, 2004) after burn injury that were not dependent upon the continual presence of elevated stress hormones and substrate loads, which suggests that intrinsic changes in the metabolism of these tissues had occurred. Such differences might be explained by changes in gene expression and enzyme protein levels; for example, sepsisinduced inhibition of gluconeogenesis has been attributed to decreased transcription of phosphoenolpyruvate carboxykinase and glucose 6-phosphatase (Deutschman et al, 1995;Maitra et al, 2000).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…1,[5][6][7][8][11][12][13][14]24,25 Flux balance analysis (FBA) uses stoichiometric and mass balance constraints to compute the intracellular fluxes. Recently, energy balance analysis (EBA) was developed to ensure the thermodynamic feasibility of the computed fluxes.…”
Section: Introductionmentioning
confidence: 99%